32-bit Filterable multi-resonator for chipless RFID tag application in sustainable smart agriculture - Azam, S. M. Kayser; Hossain, A K M Zakir; Abd. Aziz, Mohamad Zoinol Abidin; Kiani, Saad Hassan; Mohamadariff, Othman (2024)
Smart agriculture, driven by big data analytics and artificial intelligence, increasingly utilizes RFID technology for efficient operations. Conventional IC chip-based RFID tags, despite their long-range identifications, pose sustainability and environmental challenges. Chipless RFID (CRFID) technology offers an eco-friendly alternative by eliminating IC chips, but its adoption is limited by low bit coding capacity relative to size. This paper presents a 32-bit compact multi-resonator designed for CRFID tag applications in smart agriculture. Developed on a Rogers 5880 substrate, the proposed resonator features a dual-functionality design, enabling high-density data encoding while filtering Wi-Fi and 5G signals for enhanced smart capabilities. With a compact size of 1.6 × 1.0 cm2, it performs identification within the 5.1–10.8 GHz frequency range, achieving a high code density of 20 bits/cm2 and a spectral density of 5.61 bits/GHz. This design supports around 4.3 billion unique CRFID tags, providing a massive data capacity for various applications in smart agriculture. By combining compactness, sustainability, and composite functionality, the proposed resonator addresses the critical limitations of current CRFID tags. It sets the stage for the mass adoption of CRFID tags in smart agriculture, enabling efficient, scalable, and environment-friendly solutions to meet the growing demands of modern farming practices.